Suction posterior capsulorhexis: an audit of 15 years' experience. Issue 3 (23rd September 2014) - Hugkulstone, Charles E
Abstract : Aims: To audit the results of 15 years' experience of suction posterior capsulorhexis (SPC) during phacoemulsification and compare the outcomes with a recently published multicentre audit of cataract surgery, the Cataract National Dataset (CND). Methods: Prospective cohort observational study. Setting: Ophthalmology department of a district general hospital. Results: Data collection ran from June 1998 to November 2013, and 866 eyes of 786 patients were included. The mean (SD) age was 70.7 (12.4) years with 62% women. Low levels of perioperative and postoperative complications were noted, and the visual outcomes at 2 weeks in this audit were significantly better than those of the CND, with 75.4% achieving a best-corrected vision of ≥6/6 and 87.3% ≥6/12, improving to 95.8% and 100%, respectively, for best-case analysis (p<0.001 for all comparisons). 99% achieved the same or a better postoperative visual acuity than preoperatively compared with 95% in the CND (p<0.001) and none lost two lines of Snellen acuity (versus 1.24%; p<0.001). Patients receiving one of the two designs of square-edged hydrophobic acrylic intraocular lenses used in this audit did not require later YAG laser treatment compared with 2.72% of those who had a polymethylmethacrylate intraocular lens (p<0.02). Biometry accuracy was within ±1.0 D of the predicted refraction in 89.3%. Conclusions: SPC, when performed by an experienced surgeon, appears to achieve better visual outcomes than the CND without causing harm to patients nor adversely affecting biometry accuracy. Use of a hydrophobic acrylic intraocular lens with SPC may avoid the need for subsequent YAG laser therapy.